(untitled) - Kern, Richard (New York, NY, 2000)
This book discusses the need for foreign language programmes to teach literacy. It suggests approaches to curriculum development using a wide range of modern media texts such as newspapers, music videos, and film as a basis for cultural analysis
Keywords: Language and languages,Literacy,Computers and literacy; Study and teaching.,Study and teaching